Síntese e caracterização de ferritas não dopadas e dopadas com Mn a partir de baterias Zn-MnO2 exauridas e suas aplicações catalíticas - Barrada, Renan Vicente (2017)
In this current research, non-doped ferrites (Fe2O3/Fe3O4) and ferrites doped with manganese (MnFe2O4(R)) were synthesized using commercial reagents (MnFe2O4(B)) and manganese recovered from spend Zn-MnO2 batteries. The cathode of spend Zn-MnO2 batteries consists mainly of MnO2 and Mn3O4 according to X-ray diffraction (XRD) analysis. Analysis by inductively coupled plasma optical emission spectrometry (ICP OES) detected the presence of zinc from the anode of the batteries. The cathode manganese was leached with 0.5 molL-1 nitric acid and used as a dopant in the synthesis of MnFe2O4(B) ferrites. The synthesized materials presented characteristics of MnFe2O4, according to X-ray diffraction (XRD). The ferrites were characterized by scanning electron microscopy (SEM) and transmission electron microscopy (TEM). In the micrographs it was verified that the materials presented particles and agglomerates with varied and irregular geometry in nanoscale. By X-ray dispersive energy (EDS) spectrometry analysis coupled to the SEM, the composition of the synthesized ferrite particles could be analyzed. It obtained the peaks of Fe and O in the sample of Fe2O3/Fe3O4, and Fe, Mn and O in the samples of MnFe2O4(R) and MnFe2O4(B). The chemical composition of ferrites was determined by dichromatometry for iron and flame atomic absorption spectrometry (F AAS) for manganese and obtaine that 66.6% of Fe to Fe2O3/Fe3O4, 56.6% of Fe and 11.5% Mn for MnFe2O4(R), and 61.5% Fe and 4.5% Mn for MnFe2O4(B). The ferrites were catalytically evaluated in the discoloration of the methylene blue dye through the heterogeneous photo Fenton process, obtaining 15.6%, 98% and 92% of dye discoloration using Fe2O3/Fe3O4, MnFe2O4(R) and MnFe2O4(B) respectively, in 120 minutes of reaction.